2004
DOI: 10.1211/0022357023204
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of patient satisfaction with pharmaceutical services in a Nigerian teaching hospital

Abstract: Objective To assess patients' satisfaction with pharmaceutical services using an“ideal referent” model, and to further explore the validity of an existing patient satisfaction instrument. Method A cross‐sectional survey was conducted with a sample of 500 outpatients recruited consecutively at the University of Benin teaching hospital, Nigeria. A self‐completion questionnaire that employed a Likert‐type scale was used. Data were used to calculate scores on a scale that ranged from 20 to 100, with an assumed mid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
26
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 15 publications
6
26
0
Order By: Relevance
“…-Were shown to contribute decisively throughout the world to the evaluation of the quality of care as well as the acceptability of pubic health programs [17]. -Have allowed better understanding of the expectations and wishes of patients from different cultural contexts and different health systems [10][11][12]35,36]. -Have proved of value in promoting change of attitudes and behaviors of health personnel [15,18].…”
Section: Discussionmentioning
confidence: 99%
“…-Were shown to contribute decisively throughout the world to the evaluation of the quality of care as well as the acceptability of pubic health programs [17]. -Have allowed better understanding of the expectations and wishes of patients from different cultural contexts and different health systems [10][11][12]35,36]. -Have proved of value in promoting change of attitudes and behaviors of health personnel [15,18].…”
Section: Discussionmentioning
confidence: 99%
“…The hypertension therapy questionnaire ('yes' or 'no' response scale) was developed for this study while assessment of patient satisfaction was based on the twenty-item questionnaire developed by Larson et al and also validated in a Nigerian study. 15,16 The patient satisfaction questionnaire was anchored on: excellent ¼ 5, very good ¼ 4, good ¼ 3, fair ¼ 2, and poor ¼ 1. In order to reduce investigator bias, pharmacy supportive staff introduced the questionnaires to the patients who were asked to complete them at home; this was also to reduce the effect of pharmacy environment on their responses.…”
Section: Outcome Assessmentmentioning
confidence: 99%
“…Based on previous reports, the patient satisfaction questionnaire was grouped into two subscales namely 'friendly explanation' and 'managing therapy'. 15,16 The pharmaceutical care intervention improved patient satisfaction with pharmaceutical services in the two components of satisfaction. The 'friendly explanation' component had mean total score of 3.48 AE 0.83 (midpoint, 3.00; range 1 to 5).…”
Section: Patient Satisfaction Assessmentmentioning
confidence: 99%
“…Earlier in 2002, some elements of pharmaceutical care activities such as medication history taking, blood pressure measurement among others was reported to have been practiced by some community pharmacists in Benin City. 17 Low satisfaction of patients with pharmaceutical services without pharmaceutical care has been reported as well. A study in Kaduna reported a deficit in practice of pharmaceutical care, a positive attitude towards pharmaceutical care and lack of competence to practice pharmaceutical care.…”
Section: Introductionmentioning
confidence: 99%